Paucity of FOXP3+ cells in skin and peripheral blood distinguishes Sezary syndrome from other cutaneous T-cell lymphomas. - Klemke, C; Fritzsching, B; Franz, B; Kleinmann, E; Oberle, N; Poenitz, N; Sykora, J; Banham, A; Roncador, G; Kuhn, A; Goerdt, S; Krammer, P; et al. (2006)
Cutaneous T-cell lymphomas (CTCL) are mainly comprised of two variants: mycosis fungoides (MF) with CD4(+) tumor cells confined to the skin and the leukemic Sézary syndrome with tumor cell spread to the blood. In this study, we investigated cutaneous expression of the regulatory T-cell (T(reg)) marker FOXP3 in 30 CTCL patients. Immunohistochemical analysis revealed significantly lower numbers of CD4(+)FOXP3(+) cells within the dermal lymphomononuclear infiltrate of Sézary patients (16% FOXP3(+) cells of CD4(+) cells) in contrast to MF (43% FOXP3(+) cells (P<0.05)) and rare types of CTCL (45% FOXP3(+) cells). Furthermore, CD4(+)FOXP3(+) T cells were also markedly reduced in the CD4(+) population within the peripheral blood of Sézary patients compared to controls as determined by fluorescence-activated cell sorter, quantitative PCR and functional analyses. The data support the conclusion that the neoplastic cells in CTCL do not express the T(reg) marker FOXP3. Our data also identify Sézary syndrome as, to our knowledge, the first reported neoplastic disease with a clear reduction in T(reg) numbers within the CD4(+) population. This lack of T(reg) might account for the more aggressive nature of Sézary syndrome compared with other CTCL.